Intravenous fluids in acute pancreatitis: a prospective study - Sony, Jithin; Sunny, Ann; Rozaria, Anthony Prakash (International Surgery Journal, 2020)
Background: Fluid therapy is the mainstay of treatment in the management of acute pancreatitis. Most guidelines recommend aggressive fluid therapy in the initial 48-72 hours. We aimed to compare the occurrence, persistence or worsening of systemic inflammatory response syndrome (SIRS) and occurrence organ failure in patients with acute pancreatitis receiving normal and high volume fluid therapy in the first 24 hours. Methods: This was a prospective observational study. Consecutive adult patients admitted with acute pancreatitis were included in the study. SIRS was defined according to the criteria. Organ failure and local complications were defined according to Atlanta classification. Patients were divided into two groups according to the rate of fluid administered in the initial 24 hours: Normal volume group which received fluids at a rate <150 ml/hour and high volume group >150 ml/hour. Results: A total 60 patients were included in the study with 30 each in the two groups. Persistence or worsening of SIRS at 48 hours was more in normal volume fluid group compared to the high volume fluid group (p=0.076). Organ failure at 48 hours was more in normal volume fluid group compared to the high volume fluid group (p=0.074). Incidence of local complications equal in both group. Conclusions: Our study did not show any statistically significant difference in outcomes in patients with acute pancreatitis receiving normal or high volume fluids in the initial 24 hours. Further multi-centric randomised control trials are required to analyze the outcomes of high and normal volume fluid resuscitation in acute pancreatitis.